COMPARISON OF TWO FORMS OF LEFT VENTRICULAR MASS INDEXATION IN PATIENTS WITH BMI GREATER THAN 25: VASCULAR CHARACTERISTICS. (June 2018) - Schiavone, M.A.; Gonzalez, S.; Kempny, P.; Ayerdi, L.; Chiavaut Svane, J.; Failo, M.; Castellaro, C.
Abstract : Objective: 1- Compare the prevalence of left ventricular hypertrophy (LVH) using traditional indexing versus height indexation to 2.7 in the entire sample 2- To compare the anthropometric and vascular characteristics among those with LVH detected with index 2.7 versus those detected with traditional indexing. Design and method: We evaluated 680 patients in the context of a cardiovascular primary prevention program (Cardiometabolic Unit, Hospital Universitario Austral), which includes measurement of anthropometric parameters, body mass index (BMI), laboratory, measurement of the PA (ESH), echocardiogram, oscillometric determination of the pulse wave velocity (PWV)(Mobil-o-Graph), measurement of the intima media thickness (IMT) in common carotid artery, and tracking of subclinical carotid and femoral atherosclerosis. The exclusion criteria were the following: BMI < 25, age < 18,  > 80 years; Secondary hypertension, history of cardiovascular disease, missing studies. Four groups were defined: Without LVH (group1), with LVH by both methods (Group2), with LVH exclusively by LVMI (group3), and by LVMI2.7 (group4). Subsequently, Age, Body Mass Index (BMI), Systolic BP (SBP), IMT, PWV and subclinical atherosclerosis were evaluated through number of plaques (n-PLC) and plate area (A-PLC) between the 4 groups Results: A total of 422 patients were included: 52.34 ± 12.43 years, 129.63 ± 16.01/84.95 ± 10.81 mmHg, BMI: 29.54 ± 16, 26.5% female, 46.4% hypertensive, 5.7% diabetics.The prevalence of LVH with LVMI was 12.3%, while with LVMI2.7 the prevalence was 14.2% (p > 0, 05). Group 1 turned out to be younger (p = 0.002), with a lower average IMT (p = 0.0104) compared to the other 3 groups. Group 2 resulted in the oldest group (p = 0.002), with the highest number of atherosclerotic plaques (p = 0.0025) and highest PWV (p = 0.00061), respecting the other 3 groups. Finally, group 4 was the group with the highest BMI (p = 0.001), highest mean of IMT (p = 0.0104) and largest A-PLC (p = 0.03). Conclusions: Those who present LVH exclusively according to Index 2.7 seem to be associated with a higher degree of obesity and an increased IMT. Given that these patients with these anthropometric and vascular risk characteristics were not detected with traditional indexation but with index 2.7, it makes us reflect on whether it would be necessary to use both in patients with BMI > 25.